2004
DOI: 10.1097/01.sla.0000103072.34708.e3
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Imprint Cytologic Evaluation of Sentinel Lymph Nodes for Lobular Carcinoma of the Breast

Abstract: The sensitivity and specificity of IIC are similar to that of intraoperative frozen section evaluation. Therefore, IIC is a viable alternative to frozen sectioning when intraoperative evaluation is required. If SLN micrometastasis is used to determine the need for further lymphadenectomy, more sensitive intraoperative methods will be needed to avoid a second operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 43 publications
8
63
0
2
Order By: Relevance
“…In contrast, the sensitivity of IIC N in the detection of lymph node metastases in patients with lobular carcinoma was only 38.7% (Tables 6, 7). Nonetheless, despite the finding that ILC metastases are more difficult to detect compared with metastases from other breast tumor types, 14 ILC metastases were identified by IIC N in 24 of 62 cases (38.7%) in the current study, thus eliminating the need for a second surgical procedure. In contrast to the findings reported by Creager et al, 14 the difference in IIC N sensitivity between IDC and ILC proved to be statistically significant in the current study (chi-square test: P ϭ 0.012).…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, the sensitivity of IIC N in the detection of lymph node metastases in patients with lobular carcinoma was only 38.7% (Tables 6, 7). Nonetheless, despite the finding that ILC metastases are more difficult to detect compared with metastases from other breast tumor types, 14 ILC metastases were identified by IIC N in 24 of 62 cases (38.7%) in the current study, thus eliminating the need for a second surgical procedure. In contrast to the findings reported by Creager et al, 14 the difference in IIC N sensitivity between IDC and ILC proved to be statistically significant in the current study (chi-square test: P ϭ 0.012).…”
Section: Discussionmentioning
confidence: 89%
“…25,26 Both of these studies concluded that the sensitivity of TIC was better for detecting macrometastases than micrometastasis. 25,26 A small study of 17 patients demonstrated that TIC was accurate in patients who had received preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Both of these studies concluded that the sensitivity of TIC was better for detecting macrometastases than micrometastasis. 25,26 A small study of 17 patients demonstrated that TIC was accurate in patients who had received preoperative chemotherapy. 27 Importantly, this study identified distinct TIC cytologic patterns in those patients treated with preoperative chemotherapy, which may confound accurate slide interpretation in this patient subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tissue fixation and, to a lesser degree, tissue processing, are potential causes of variation in the reproducibility of immunohistochemical staining [28]. Above and beyond that, in cytologic preparations, the cells are whole, a larger surface of the tumor is sampled, and tissue is preserved for subsequent pathological and molecular analyses [27,[29][30][31]. It is now firmly established that a wide variety of markers can be applied on cytologic preparations and that immunocytochemistry correlates well with immunohistochemistry [32][33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%